Novel technique of controlled laser air-force detection for rheological properties of polymers - Xu, Hubo; Hu, Ruizhi; Lin, Yingzi; Juan, Hincapie; Tang, Xiuying (International Journal of Agricultural and Biological Engineering, 2022)
A novel controlled laser air-force detection (CLAFD) technique was developed to detect the rheological properties of polymers with the characteristics of non-destruction and cross-contamination free. Dynamic testing and static testing were carried out in the technique. Back propagation neural network algorithm was used to establish the air-force control model. The replicability of CLAFD system was analyzed, the viscoelastic properties of polyurethane were investigated using alternating load testing. A comparative analysis of performances was made between the CLAFD and the texture analysis (TA) on the testing of creep-recovery and stress relaxation. The results demonstrated that the CLAFD system had good replicability. The lagging phase angle was between 0°-90° in the testing of alternating load. This illustrated that the CLAFD technique could be used to detect viscoelasticity. The parameters of response speed and the precision of the CLAFD entirely surpassed the TA on the creep-recovery testing. The CLAFD technique will provide a new real-time, non-destruction and cross-contamination-free detection method for material science, especially for those materials such as artificial biological tissue and function food products. Keywords: controlled laser air-force detection (CLAFD) technique, biological tissues, rheological properties, statics analysis, dynamic analysis DOI: 10.25165/j.ijabe.20221501.6494 Citation: Xu H B, Hu R Z, Lin Y Z, Juan H, Tang X Y. Novel technique of controlled laser air-force detection for rheological properties of polymers. Int J Agric & Biol Eng, 2022; 15(1): 62–70.